PENGARUH SITUS BERITA ONLINE DETIK.COM TERHADAP PEMENUHAN KEBUTUHAN INFORMASI SELAMA MASA PANDEMI COVID-19 PADA MAHASISWA ILMU KOMUNIKASI FIS UNJ ANGKATAN 2019 - Yesi Andriani; K. Y.S. Putri (Universitas Baturaja, 2021)
This study aims to see the effect of the online news site Detik.com on the fulfillment of information needs during the Covid-19 pandemic for student of the 2019 FIS UNJ Communication Science. In the research, the population of the 2019 FIS UNJ Communication Science student was used. Simple random sampling used in this study and from the calculation results obrained a sampling of 45 respondents. The results showed that the simple linear regression equation is Y=-0,105 + 0,988X with a significant result of 0,000. Thus, there is an influence between the online news site Detik.com and the fulfillment of information needs during the Covid-19 pandemic.